Answer to ECG Quiz no. 33 - Millar, R. Scott (SA Heart Journal, 2017)
Rapid, bizarre complexes on ECG may be due to artefact. Occasionally, P-waves may be larger than QRS complexes, especially in very abnormal hearts. Muscle tremor from Parkinson’s mimics atrial flutter, but normal P-waves are visible in less affected leads.